Cultural concepts employed in child discipline within rural Yorùbá households: the Ayetoro-Oke African community. Issue 2 (4th May 2017) - Busari, Dauda Aderemi; Owojuyigbe, Michael A.; Okunola, Rasidi A.; Mekoa, Itumeleng
Abstract : Social scientists have long been concerned about social control, not only of adults, but also of children. In recent years, however, concerns have escalated globally, particularly regarding the lack of integration of indigenous knowledge about many aspects of children's upbringing. The present research addresses knowledge gaps around aspects of the Yorùbá culture employed in rural African communities to ensure child discipline, and consequently social control among all members. Employing a descriptive case study research design, we describe the cultural concepts employed as instruments of child discipline within households in the Ayetoro-Oke community of Oyo state. Using 6 focus group discussions involving 45 persons across the community, we identify and describe 7 cultural elements employed in child training within the households in the rural community, ranging from "Ijiya" (punishment) to "Orin" (songs). The article concludes shaming is a key element upon which such cultural concepts are built and guides child discipline among the people of Ayetoro-Oke. It also notes differences between traditional discipline and western child-rearing practices may lead to potential conflict in attempting to integrate the indigenous with the modern. It concludes by suggesting the use of indigenous knowledge in developing parts of societal life is warranted, and based on the findings, recommends areas requiring future research.